Patient & public involvement for inherited cardiac conditions. (29th July 2021) - Bueser, T; Patch, C; Rowland, E; Coles, L; Metcalfe, A
Abstract: Funding Acknowledgements: National Institute for Health Research OnBehalf: King"s Health Partners Patient & Public Involvement for Inherited Cardiac Conditions (PPIICC) group Background: Inherited Cardiac Conditions (ICCs) affect up to 1:200 of the population and is the leading cause of sudden death in the under 40s. Research into developing interventions to support patients as they adjust to their diagnosis and genetic carrier status is underway; an example of which is the Psychoeducational Intervention Supporting patients with an ICC (PISICC) study. To ensure the appropriateness, acceptability and applicability of the intervention, patients and the public were involved in the development of PISICC intervention. Purpose: To ensure the relevance and improve the quality of the PISICC study, Patient & Public Involvement for Inherited Cardiac Conditions  (PPIICC) group was organised to guide the research project as this progressed through the three phases of the Medical Research Council framework for developing complex interventions. Methods: Utilising INVOLVE guidelines, the PPIICC group was initiated by the researcher by inviting patients and families attending a local ICC clinic, members of the patient support group, Cardiomyopathy UK; and members of the existing PPI group of the local biomedical research centre. Ground rules, terms of engagement and provisions for meetings such as rooms, reimbursements for transport costs, childcare and compensation for time was established. The PPIICC group met up to three times per year within a three-year period with electronic exchanges in between. Members gave individual feedback to draft study materials and their views shaped the final versions. A modified Delphi study was used for the development of the PISICC intervention model. Figure 1 illustrates the activities undertaken by the group. Results: The involvement of the PPIICC group throughout the development of the PISICC intervention model has contributed to the successful recruitment of 32 participants and completion of the qualitative study in Phase 1. In Phase 2 the group had a crucial role in ensuring that the education component of the PISICC intervention included  advice on medication and physical activity; and for the group component of the intervention to include a mixed age group to enable sharing of varied experiences. In planning for Phase 3, the PPIICC group helped ensure that the trial processes for the planned feasibility study were not burdensome to participants which supported its full ethical approval by the UK Health Research Authority. Conclusions: Patients and their families played an important role in designing the PISICC study. So far, their involvement has resulted in reaching recruitment targets for Phase 1 of the study, the development of a patient-informed psychoeducational intervention model and feasibility study protocol.